Tiny toon adventures. Season 1, volume 2 [videorecording (DVD)] (Distributed by Warner Home Video, 2009)
Take a loopy look at Acme students who get a hire education by seeking part-time jobs. A minaturized Babs and Buster tour Plucky's brain. Game-show bachelors Hamton, Plucky and Montana Max woo (un)lucky bachelorette Elmyra. Waiter Plucky takes an order for duck à l'orange. Various Toonsters battle monsters, solve mysteries, rock out in music videos, roll back to prehysteric prehistory and more.